Communication of The Indonesian Government To The Television Broadcasting Industry Regarding The Policy On Digitization - Desliana Dwita; Sjuchro, Dian Wardiana; Hidayat, Dadang Rahmat; Sjafirah, Nuryah Asri (International Journal of Global Community, 2021)
The Indonesian government has informed television broadcasting industry since 2007 regarding the policy of migration from analog to digital technology by inviting television associations in joint meetings and discussion forums. However, the efforts that have been made by the government have not been able to make the television broadcasting industry have the same construction on the policy of television digitization to jointly realize it. This study aims to analyze and reveal the reality of the Indonesian government’s communication to the television broadcasting industry regarding the policy on terrestrial television digitization. The method used is qualitative with the type of case study and constructivist paradigm. This study reveals that there is uncertainty with the reality of the Indonesian government’s communication to the television broadcasting industry regarding terrestrial television digitization policies in 2007-2018, and there is no maximum time to explain issues about television digitization which are very technical. In addition, participatory communication is not fully carried out by the government to invite the television broadcasting industry to participate in the success of accelerating the terrestrial television digitization in Indonesia.